Preparation and Thermal Stability of Nano-Sized HMX-Based Polymer Bonded Explosives. Issue 8 (11th June 2023) - Zhang, Zhimiao; Cao, Xinfu; Gao, Jianbing; Chen, Yong; Wang, Deqi; Qin, Yang; Sun, Sensen; Yu, Haomiao; Liu, Jie; Deng, Guodong; Li, Fengsheng
ABSTRACT: In this study, M-HMX-based PBX (M-HMX-PBX) and N-HMX-based PBX (N-HMX-PBX) were prepared by industrial micron-sized HMX (M-HMX) and nano-sized HMX (N-HMX) via solution-water suspension method, respectively. The critical electronic excitation energy ( Ec ) of M-HMX particle and N-HMX particles was calculated by combining with field emission scanning electron microscopy (FE-SEM) and Image Pro Plus (IPP) software. Meanwhile, the average critical electron excitation energy ( E C ‾ ) of the entire particle group was calculated. Those results shown that E C ‾ of N-HMX was higher than that of M-HMX, which indicated that the stability of N-HMX was better than that of M-HMX. In addition, the reaction activation energies ( Ea ) also indicated that N-HMX and N-HMX-PBX were more stable than M-HMX and M-HMX-PBX, which were calculated by the Kissinger-Akahira-Sunose (KAS) and Flynn-Wall-Ozawa (FWO) methods. The above results explained the reasons for the high thermal decomposition stability of N-HMX-PBX from the micro and macro perspectives. And those provided theoretical basis for exploring the application of N-HMX in improving the thermal stability of HMX-PBX.